Patient-Reported and Quantitative Outcomes of Anatomic Anterior Cruciate Ligament Reconstruction With Hamstring Tendon Autografts - Diermeier, Theresa (Orthop J Sports Med, 2020)
BACKGROUND: The pivot-shift test has become more consistent and reliable and is a meaningful outcome measurement after anterior cruciate ligament reconstruction (ACLR). PURPOSE/HYPOTHESIS: The purpose of this investigation was to assess patient-reported outcomes (PROs) and the quantitative pivot shift (QPS) preoperatively, at time zero immediately after anatomic ACLR, and after 24 months as well as the relationship between PROs and the QPS. It was hypothesized that anatomic ACLR would restore rotatory stability measured by the pivot-shift test and that QPS measurements would be positively correlated with PROs. STUDY DESIGN: Cohort study; Level of evidence, 2. METHODS: The ACL-injured and contralateral uninjured knees from 89 of 107 (83.2%) enrolled patients at 4 international centers were evaluated using a standardized pivot-shift test. Tibial acceleration was assessed with an inertial sensor, and lateral compartment translation was measured using an image analysis system preoperatively, at time zero immediately postoperatively, and at follow-up after 2 years. PROs were assessed at 12 and 24 months postoperatively with the International Knee Documentation Committee (IKDC) subjective knee form, Cincinnati Knee Rating System (CKRS), Marx activity rating scale, and activity of daily living score (ADLS). RESULTS: The mean patient age at surgery was 27 years (range, 15-45 years). A positive pivot shift preoperatively (side-to-side difference in tibial acceleration, 2.6 ± 4.0 m/s(2); side-to-side difference in anterior tibial translation, 2.0 ± 2.0 mm) was reduced at time zero postoperatively (side-to-side difference in tibial acceleration, –0.5 ± 1.3 m/s(2); side-to-side difference in anterior tibial translation, –0.1 ± 1.0 mm). All PROs improved from preoperatively to final follow-up at 24 months: from 56.5 to 85.5 points for the IKDC (P = .0001), from 28.8 to 32.4 points for the CKRS (P = .04), from 11.2 to 7.9 points for the Marx (P < .0001), and from 75.7 to 91.6 points for the ADLS (P < .0001). Neither preoperative nor time zero postoperative rotatory laxity assessed by the pivot-shift test correlated with PROs at 24-month follow-up. A graft retear was observed in 4 patients (4.5%) within 2 years of follow-up. CONCLUSION: Anatomic ACLR resulted in significantly improved and acceptable PROs at 2-year follow-up and a low failure rate. Anatomic ACLR restored QPS measurements of anterior tibial translation and tibial acceleration to those of the contralateral knee immediately after surgery while still under anesthesia, but there was no correlation between the QPS preoperatively or at time zero after ACLR and PROs at 2-year follow-up.